PENGARUH KUALITAS PRODUK, INOVASI PRODUK DAN BRAND IMAGE TERHADAP KEPUASAN KONSUMEN (STUDI PADA BUBUR AYAM CIANJUR DI KOTA BOGOR) - Maslahat Maslahat; Irmal Irmal (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to examine the effect of Product Quality (X₁), Product Innovation (X₂), and Brand Image (X₃) on Consumer Satisfaction (Y) at Bubur Ayam Cianjur in Bogor City. A quantitative method was employed, with 96 consumers as respondents, selected using probability sampling and Row Purba’s formula. Data were analyzed through regression analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The results indicate that Product Quality, Product Innovation, and Brand Image have a significant and positive effect on Consumer Satisfaction, with the regression equation Y = 6.115 + 0.437X₁ + 0.424X₂ – 0.014X₃. The correlation coefficient of 0.721 indicates a strong relationship, and the coefficient of determination shows that the three variables simultaneously explain 52% of the variation in consumer satisfaction. The simultaneous hypothesis test yielded F = 33.207 > F table = 2.700, confirming that Product Quality, Product Innovation, and Brand Image simultaneously and positively influence Consumer Satisfaction.